Une socialisation professionnelle par l’histoire : la formation morale des Saint-Cyriens et le martyrologe patriotique - Alex Alber (Temporalités)
Using data gathered while researching the Special Military Academy (École Spéciale militaire) of Saint-Cyr Coëtquidan in 2002, this article shows that the training of future French officers can be subdivided into three different sorts of instruction : military, academic and “moral”. The interest of the latter is that it seems to take advantage of the transmission of the memory of former officers having laid down their lives for France as a means to reinforce the cadets’ patriotism. The article points to the fact that cadets are often already convinced of the importance of patriotism and other military values upon entering the military academy. Moreover, with the passage of time, the cadets’ enthusiasm for bravery and sacrifice seems to cool slightly, as they slowly become more realistic about their commitment.